Subjek Hukum Kegiatan Pengelolaan Rumah Susun Bukan Hunian: Pasar Sentral Ujung Pandang - M. Ridjal Adelansyah Syam; Farida Pattitingi; Sri Susyanti Nur (SIGn Jurnal Hukum, 2022)
This study examines and analyzes the legal subject of the Ujung Pandang Central Market management activities, which are treated as Non-Residential Condominium buildings based on Law No. 20 of 2011. This research combines normative juridical and empirical research methods. The primary data were collected using direct interviews, while the secondary data was collected using literature study techniques. The data obtained in this research were then analyzed qualitatively. The results show that the legal subject of the Ujung Pandang Central Market management activities, which are treated as Non-Residential Condominium buildings, must be held by PPPSRS based on Article 59 of Law No. 20 of 2011. In this case, if PPPSRS has not been established, then PT. MTIR must establish PPPSRS no later than one year from the first delivery of the condominium unit to the owner. However, until now, PPPSRS has not been established and established by PT. MTIR. So strictly speaking, PT. MTIR deviated from its obligations in implementing Law No. 20 of 2011. Therefore, it is recommended that the Makassar Municipal Government re-evaluate the involvement of PT. MTIR as Holder of The Right to Build for Ujung Pandang Central Market. In addition, it is recommended to PT. MTIR to comply with Article 59 of Law No. 20 of 2011 by establishing PPPSRS. Furthermore, it is hoped that law enforcement and the Regional House of Representatives of Makassar Municipal will protect the interests of traders so that PPPSRS is established as a legal subject for the Ujung Pandang Central Market management activities.